GYMNASTICS RELATIONSHIP WITH OLD PREGNANT ON LABOR STAGE 1 PRIMIPAROUS AT BPM RISFAJANI AM.KEB POKOH MENDEN KEBONARUM KLATEN YEAR 2013 - Aulia .; Yunisa .; Maryanti . (STIKES DUTAGAMA KLATEN, 2014)
Background: Partus is the process whereby the baby, placenta and amniotic membranes out of the womb. Maternity coverage in Indonesia by skilled health personnel has increased significantly from 61.4% in 2007 to 87.4% in 2011. Pregnancy exercise is exercise that is done during pregnancy in order to physically and mentally prepare pregnant women, in the hope the birth will go smoothly and safely. Based on data from a preliminary study in January to September 2012 as many as 90 women giving birth, 63 mothers doing pregnancy exercise and 27 pregnant mothers do not do gymnastics. Objective: To determine the relationship of pregnancy exercise with a long stage of labor in primipara 1. Research methods: The research was an analytic observational cohort study design and approach of retrospective time. Statistical tests using a simple test that Relative Risk. In the entire study population, maternal primiparity. The samples in this study were all women giving birth who meet the inclusion and exclusion criteria. Sampling purposive sampling with a sample population of 63 respondents and 39 maternal primiparous. The results: of the 39 respondents shows that there are 24 respondents (61.5%) of pregnant mothers do gymnastics and 15 respondents (38.5%) did not do gymnastics pregnant. Which means that pregnant women who routinely perform exercises while pregnant whit faster opening speeds 20 times faster than during pregnancy in women who don’t carry pregnancy exercise. Conclusion: There is a relationship between pregnancy exercise with a long stage of labor 1 in primipara. Keywords: pregnancy exercise, long stage of labor 1, primiparous